Analytical and scientific support mechanism of the US foreign policy process - I. A. Istomin (Vestnik MGIMO-Universiteta)
The U.S. intellectual leadership in many spheres is rarely challenged nowadays. However it is secured not only through the ability to formulate a great amount of new ideas, including fundamental innovations, but perhaps even more due to the effective system for integration of intellectual products into practice. Nevertheless this is hardly a research issue for Russian scholars. The article is an attempt to take a closer look on design and behavior of principal channels and institutions, employed by American scholars and experts for participation in shaping national foreign policy.